Effect of foliar application of fulvic acid antitranspirant on sugar accumulation, phenolic profiles and aroma qualities of Cabernet Sauvignon and Riesling grapes and wines. (30th July 2021) - Li, Wanping; Yao, Heng; Chen, Keqin; Ju, Yanlun; Min, Zhuo; Sun, Xiangyu; Cheng, Zhenglong; Liao, Zusong; Zhang, Kekun; Fang, Yulin
Graphical abstract: Highlights: FA-AT controlled the sugar of grapes and alcohol of wines. FA-AT improved the total tannin and individual flavanols in CS grape and wine. The increased volatiles in CS grape and wine can contribute to fruity and floral aroma. The reduction of anthocyanins by FA-AT did not affect the tonality of wine. Sensory analysis revealed the treated wines presented advantageous characteristics. Abstract: This study investigated the effects of foliar application of fulvic acid antitranspirant (FA-AT) on Cabernet Sauvignon (CS) and Riesling grapes and wines in a warm viticulture region of China. FA-AT controlled the contents of total soluble solids, fructose and glucose in mature grapes and alcohol in wines. FA-AT improved total phenols and flavonoids in Riesling grapes, and total tannin and individual flavanols in CS grapes and wine, while reducing total individual phenolic acids and flavonols in CS wine. Increased volatiles in CS grapes (hexyl acetate, linalool) and wine (isoamyl alcohol, 1-hexanol, 2-phenylethanol) detected by SPME–GC–MS can contribute to the fruity and floral aroma. FA-AT reduced the accumulation of anthocyanins in CS grapes and wine without an eventual reduction in the tonality of wine by sensory analysis, and improved the taste and balance of Riesling wine. Overall, FA-AT can improve the quality of grapes and wines produced in warm viticulture regions.